Causes and management of job stress among selected teachers in Cameroon (Journal for Studies in Humanities and Social Sciences, 2015)
This paper looks at the causes of job-related stress among teachers of Buea - Cameroon, and individual management strategies they employ. The study uses the chi-square test that reveals the main causes of stress among teachers are i) student indiscipline, ii) poor salary situations, iii) a sense of under-promotion, iv) heavy work load, and v) conflicting relationship with principals. The paper purports that socio-economic factors are the most important predictors of stress, followed by interpersonal relations and then by instructional problems. Individual personality differences and social support systems moderate the impact of stressors on teachers, influence their appraisal of socio-environmental demands as stressful, and determine the effectiveness or ineffectiveness of the coping strategies generated to manage job stress.